Spin-active defects in hexagonal boron nitride. (1st September 2022) - Liu, Wei; Guo, Nai-Jie; Yu, Shang; Meng, Yu; Li, Zhi-Peng; Yang, Yuan-Ze; Wang, Zhao-An; Zeng, Xiao-Dong; Xie, Lin-Ke; Li, Qiang; Wang, Jun-Feng; Xu, Jin-Shi; et al.
Abstract: Quantum technology grown out of quantum information theory, including quantum communication, quantum computation and quantum sensing, not only provides powerful research tools for numerous fields, but also is expected to go to civilian use in the future. Solid-state spin-active defects are one of promising platforms for quantum technology, and the host materials include three-dimensional diamond and silicon carbide, and the emerging two-dimensional hexagonal boron nitride (hBN) and transition-metal dichalcogenides. In this review, we will focus on the spin defects in hBN, and summarize theoretical and experimental progresses made in understanding properties of these spin defects. In particular, the combination of theoretical prediction and experimental verification is highlighted. We also discuss the future advantages and challenges of solid-state spins in hBN on the path towards quantum information applications.